2016
DOI: 10.1111/ane.12709
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in stroke survivors: A 10-year follow-up study

Abstract: Post-stroke cognitive impairment was prevalent among 10-year stroke survivors, and the odds of having severe cognitive impairment were higher among the stroke survivors compared to non-stroke persons. The burden of long-term PSCI might have been underestimated previously, and MoCA may be more suitable than MMSE to detect long-term PSCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 39 publications
(107 reference statements)
0
64
0
3
Order By: Relevance
“…The MoCA has been frequently used in studies which explored the evolution of post-stroke cognitive impairment. Recently, Delavaran et al (2016) have reported that 61% of stroke patients with a median NIHSS at baseline of 3 had cognitive impairment 10-year post-stroke. They suggested that the MoCA was more accurate in the detection of long-term post-stroke cognitive impairment as compared to other scales such as the Mini-Mental State Evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The MoCA has been frequently used in studies which explored the evolution of post-stroke cognitive impairment. Recently, Delavaran et al (2016) have reported that 61% of stroke patients with a median NIHSS at baseline of 3 had cognitive impairment 10-year post-stroke. They suggested that the MoCA was more accurate in the detection of long-term post-stroke cognitive impairment as compared to other scales such as the Mini-Mental State Evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The LSR has been previously described in detail [10, 15]. To detect first-ever stroke patients, research nurses in the LSR perform “hot pursuit” of stroke cases through daily weekday screenings of patient lists from the Emergency Department as well as in- and outpatient lists at the Department of Neurology at SUS Lund.…”
Section: Methodsmentioning
confidence: 99%
“…Both MMSE and MoCA have been translated into Chinese and validated as a screening tool for cognitive impairment and dementia in the Chinese population; the maximum score is 30 for these 2 measurements. According to the recommended cutoffs, cognitive function was categorized as follows: 0 to 22 (severe cognitive impairment), 23 to 26 (mild cognitive impairment), and 27 to 30 (no cognitive impairment) for MMSE scores; 0 to 19 (severe cognitive impairment), 20 to 24 (mild cognitive impairment), and 25 to 30 (no cognitive impairment) for MoCA scores . In this analysis, a score of <27 on the MMSE and <25 on the MoCA indicated cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%